The potential of tailoring the conditions of steam explosion to produce xylo-oligosaccharides from sugarcane bagasse - Carvalho, Ana Flavia Azevedo [UNESP] (2018)
In this study, the potential of the steam explosion (SE) method to produce high levels XOS from sugarcane bagasse, a xylan-rich hemicellulosic feedstock, was assessed. The effect of different operating conditions on XOS production yield and selectivity were investigated using a mini-pilot scale SE unit. The results show that even under a non-optimized condition (190 °C, 5 min and 0.5% H2SO4 as catalyst), SE led to about 40% xylan recovery as XOS, which was comparable to the well-known, multi-step, enzymatic production of XOS from alkaline-extracted xylan, and other commonly employed chemical methods. In addition, the XOS-rich hydrolysate from SE constituted of greater diversity in the degree of polymerization, which has been shown to be desirable for prebiotic application.